Tertiary Alkylative Suzuki–Miyaura Couplings - Tsuchiya, Naoki; Sheppard, Tom D.; Nishikata, Takashi (Synthesis, 2022)
Suzuki–Miyaura coupling is an extremely useful way to construct Csp2–Csp2 carbon bonds. On the other hand, Csp2–Csp3 coupling reactions do not work well, and tert-alkylative Suzuki–Miyaura coupling is particularly challenging due to problematic oxidative addition and β-hydride elimination side reactions. In this short review, we will introduce recent examples of tert-alkylative Suzuki–Miyaura couplings with tert-alkyl electrophiles or -boron reagents. The review will mainly focus on catalyst and product structures and on the proposed mechanisms.1 Introduction2 Ni-Catalyzed tert-Alkylative Couplings3 Pd-Catalyzed tert-Alkylative Couplings4 Fe-Catalyzed tert-Alkylative Couplings5 tert-Alkylative Couplings with 1-Alkenyl Borons6 tert-Alkylative Couplings under Photoirradiation7 Stereospecific tert-Alkylative Couplings8 Conclusion
Keywords: radical; tert-alkyl; Suzuki–Miyaura coupling; SET; stereospecific reactions